Disseminated BCG: Complications of Intravesical Bladder Cancer Treatment - Uyen To; Joyce Kim; David Chia (Case Reports in Medicine)
Intravesical bacillus Calmette-Guerin (BCG) has been established as an effective treatment of superficial bladder cancer (Parker and Kommu, 2013). However, major side effects, including pneumonitis, sepsis, and even death, may occur in <5% of patients (Gonzalez et al., 2003). Here we present a case of severe disseminated Mycobacterium bovis following intravesical BCG administration. Our patient is a 76-year-old gentleman with newly diagnosed superficial transitional cell carcinoma of the bladder who recently received his first intravesical BCG treatment. He initially presented with hemoptysis and was found to have extensive patchy infiltrates bilaterally. He was treated for pneumonia with antibiotics and then with steroids for hypersensitivity pneumonitis but continued to deteriorate. Due to the temporal proximity of his exposure to BCG, we administered treatment for presumed disseminated BCG infection with rifampin, isoniazid, and ethambutol. Within a 48-hour period, the patient improved dramatically. The reported cases of infection from intravesical BCG illustrate an insidious onset with initial symptoms of low-grade fevers and cystitis but may progress to pneumonitis. If the symptoms persist for more than 7 days or if there is clinical deterioration, RIPE therapy (with rifampin, isoniazid, pyridoxine, and ethambutol) and a fluoroquinolone should be administered for a 6–9-month course along with steroids for 4–6 weeks (Naudžiunas et al., 2012).